2018
DOI: 10.1096/fj.201801845r
|View full text |Cite
|
Sign up to set email alerts
|

Trained murine mesenchymal stem cells have anti‐inflammatory effect on macrophages, but defective regulation on T‐cell proliferation

Abstract: Mesenchymal stem cell (MSC)‐mediated immunomodulation affects both innate and adaptive immune systems. These responses to environmental cues, such as pathogen‐associated molecular patterns, damage‐associated molecular patterns, or proinflammatory cytokines, are crucial for resolution of inflammation, as well as successful tissue healing and regeneration. We observed that intermittent, repeated exposure of MSCs to LPS induced stronger NF‐κB activation than singular stimulation. A similar phenomenon, named innat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Several authors have noted an increase in the antigen-presenting properties of MSCs as a result of IFN-γ pretreatment [72]. Other studies have shown that the "priming" of MSCs in vitro with IFN-γ, TNF-α, or IL-1β leads to the formation of the immunosuppressive phenotype MSC-2 [47,73,74]. Our results showed, for the first time, that after administration in mice, modified MSCs treated with IFN-γ cause a pronounced (tenfold) decrease in the cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have noted an increase in the antigen-presenting properties of MSCs as a result of IFN-γ pretreatment [72]. Other studies have shown that the "priming" of MSCs in vitro with IFN-γ, TNF-α, or IL-1β leads to the formation of the immunosuppressive phenotype MSC-2 [47,73,74]. Our results showed, for the first time, that after administration in mice, modified MSCs treated with IFN-γ cause a pronounced (tenfold) decrease in the cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a pre-conditioning protocol for MSCs using short-term exposure of MSCs to TNFα and lipopolysaccharide (LPS) to enhance immunomodulation (by promoting polarization to an anti-inflammatory macrophage phenotype) and osteogenesis [178]. In addition, training MSCs by exposure to inflammatory cytokines and other substances appears to impart an innate immune memory of the prior stimulus [179]. We have also developed NF-κB sensing and IL-4 over-expressing genetically modified MSCs to treat chronic inflammation [176,180].…”
Section: Cell Therapymentioning
confidence: 99%
“…Finally, stromal cells, which include fibroblasts and endothelial cells, also show memory to previous stimuli (reviewed in Reference ). Coculture of macrophages with LPS‐trained bone marrow‐derived mesenchymal stem cells in vitro led to reduced proinflammatory and enhanced anti‐inflammatory responses in the macrophages, which was associated with epigenetic alterations in the mesenchymal stem cells mesenchymal stem cells . The longevity of this effect was not determined but considering that mesenchymal stem cells are distributed in the perivascular niche of most tissues, microbial‐induced memory in these cells could be instrumental in defining immune responses.…”
Section: Microbiome and Innate Memorymentioning
confidence: 99%